Relación de los contenidos periodísticos sensacionalistas con la divulgación de la inmediatez informativa caso: Periodismo digital del cantón Quevedo, año 2022 - Torres Monteset, Akira Mariana (2022)
The contribution of information and communication technology (ICT) has made it possible to manage a journalism for the dissemination of computer immediacy, such as digital journalism, which is at the forefront and where anyone with a digital device can transmit any type of information. without knowing where the information comes from. The objective of this project is to determine the relationship between sensationalist journalistic content and the dissemination of informative immediacy "case: digital journalism in the Quevedo canton. For the development of the investigative process, the survey technique was used through which a questionnaire of questions was applied to the citizens. Concluding that journalism has evolved rapidly, adapting perfectly to the new computer age through which it has all the tools at its disposal to carry out quality journalism, however, many of them use sensational content with the intention of obtaining more followers. and that the information that is presented goes viral quickly through digital journalism that is highly popular and accepted among users.